Evaluation of the Implementation of the Pancasila Student Profile Strengthening Project at SMK Negeri 2 Yogyakarta, SMK 5 Negeri Yogyakarta, and SMK Negeri 6 Yogyakarta - Entin Hardini Waluyo; Udik Budi Wibowo (FKIP - Universitas Riau, 2026)
This study is an evaluation study with a qualitative approach that aims to gain an in-depth understanding of the implementation of the Pancasila Student Profile Strengthening Project (P5) through scientifically sound procedures that are academically accountable. Data collection was carried out through in-depth interviews, observations, and documentation involving the principal, vice principal for curriculum, P5 coordinator, teachers, and students. Data analysis used the Miles, Huberman, and Saldaña model, which includes the stages of data collection, data reduction, data presentation, and conclusion drawing. Data validity was ensured through the criteria of credibility, transferability, dependability, and confirmability as proposed by Lincoln and Guba. The results showed that the implementation of P5 in the three schools had different characteristics. SMK Negeri 2 Yogyakarta implemented P5 during the transition to the Merdeka Curriculum with various challenges, such as limited initial understanding, schedule conflicts, and uneven teacher and facility readiness. SMK Negeri 5 Yogyakarta viewed P5 as a continuation of project-based learning with flexible implementation, although it still faced coordination challenges and variations in student work speed. Meanwhile, SMK Negeri 6 Yogyakarta showed more stable and systematic readiness with institutional support and the involvement of parents and industry. In general, P5 contributed to the gradual and long-term strengthening of students' character and skills.